2016
DOI: 10.1093/glycob/cww098
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking sialyltransferase ST3Gal-II develop late-onset obesity and insulin resistance

Abstract: Sialyltransferases are a family of 20 gene products in mice and humans that transfer sialic acid from its activated precursor, CMP-sialic acid, to the terminus of glycoprotein and glycolipid acceptors. ST3Gal-II (coded by the St3gal2 gene) transfers sialic acid preferentially to the three positions of galactose on the Galβ1-3GalNAc terminus of gangliosides GM1 and GD1b to synthesize GD1a and GT1b, respectively. Mice with a targeted disruption of St3gal2 unexpectedly displayed late-onset obesity and insulin res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…For the 7 enzymes in this category, obesity of KO mice from published St3gal2, Glrx2, Hdac6 and Prdx6 KO lines agrees with our data. 153–157 Obesity of KO mice from published Gpx7 and Adamts18 KO lines 158 , 159 is consistent with our data and with GWAS data linking obesity to GPX7 158 and to ADAMTS18 which is closely associated with a BMI cluster ( Table 6 ), but not with the absence of obesity in independent Gpx7 and Adamts18 KO lines studied in the IMPC HTS. Our HTS data for Usp13 KO mice are consistent with the obesity of female mice from an independent IMPC Usp13 KO line.…”
Section: Resultssupporting
confidence: 90%
“…For the 7 enzymes in this category, obesity of KO mice from published St3gal2, Glrx2, Hdac6 and Prdx6 KO lines agrees with our data. 153–157 Obesity of KO mice from published Gpx7 and Adamts18 KO lines 158 , 159 is consistent with our data and with GWAS data linking obesity to GPX7 158 and to ADAMTS18 which is closely associated with a BMI cluster ( Table 6 ), but not with the absence of obesity in independent Gpx7 and Adamts18 KO lines studied in the IMPC HTS. Our HTS data for Usp13 KO mice are consistent with the obesity of female mice from an independent IMPC Usp13 KO line.…”
Section: Resultssupporting
confidence: 90%
“…Knockout of ST3Gal-II ( 9 ) reduces GD1and GT1b levels in the brain by 50%, whereas brain-protein sialylation is unchanged [ 35 ]. A loss of ST3Gal-II also leads to late-onset obesity and insulin resistance [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Deletions in ZPLD1 were proven to contribute to the genetic susceptibility of common childhood obesity [ 44 ]. Mice lacking ST3GAL2 (ST3 beta-galactoside alpha-2,3-sialytransferase 2) have 50 % more fat mass and 9 % more lean body mass than the control [ 45 ]. ZGRF1 (Zinc finger GRF-type containing 1) encodes a protein that contains GRF zinc finger (zf-GRF) and transmembrane domains, and a recent genome-wide and exome chip association study revealed that the gene is associated with adiposity [ 46 ].…”
Section: Discussionmentioning
confidence: 99%